Smart Greenhouse Design Based Internet of Things (IoT) With Microcontroller Arduino Uno - Maria Marli Natonis; Lidia Lestari Kitu Manu; Priska Maria Cicilia Amleni; Darsono Nababan; Yoseph P.K Kelen; Willy Sucipto (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2023)
not spread evenly among the people. Most people still use traditional methods and depend on the uncertain climate to meet their food needs, such as vegetables and fruits. Based on this, an Internet of Things (IoT) based Smart Greenhouse Design with Arduino Uno Microcontroller was created as a solution that is expected to help make it easier for farmers to cultivate plants. The greenhouse is a building that has the function to protect plants from external disturbances such as pests, heavy rain, strong winds, and excessive humidity. Meanwhile, what is called a smart greenhouse that uses technology such as the Internet of Things (IoT), is designed to automatically monitoring uses the Arduino Uno microcontroller as the control center for each sensor used, namely DHT22 (air temperature and humidity sensor), Soil Moisture (soil moisture sensor), GUVA-S12SD (UV light intensity sensor). The sensor will obtain the required data and will be automatically sent to the server (blynk application) with the help of ESP8266 (wifi module). The method used in this study is engineering design in the manufacture of the automation system. The results of this research are in the form of a smart greenhouse that can regulate, adjust, and modify the climate to optimize the conditions and processes of plant growth in the greenhouse equipment through microcontrollers and monitoring devices such as sensors and can be controlled remotely via mobile phones or computers everywhere.